Modulation effects of microorganisms on tea in fermentation - Hu, Ting; Shi, Shuoshuo; Ma, Qin (Frontiers in Nutrition, 2022)
Tea is a popular traditional drink and has been reported to exhibit various health-promoting effects because of its abundance of polyphenols. Among all the tea products, fermented tea accounts for the majority of tea consumption worldwide. Microbiota plays an important role in the fermentation of tea, which involves a series of reactions that modify the chemical constituents and thereby affect the flavor and bioactivities of tea. In the present review, the microorganisms involved in fermented tea and tea extracts in the recent studies were summarized and the modulation effects of microorganisms on tea in fermentation, including polyphenols composition and content, biological activities and sensory characteristics, were also critically reviewed. It is expected that the data summarized could provide some references for the development of microbial fermented tea drinks with specific nutrition and health benefits.